(untitled) (Journal of Science and Technology, 2016)
This paper examined the level of knowledge sharing among staff of the KNUST Library. Forms in which knowledge sharing manifest itself and should manifest itself in the Library were also investigated. Questionnaires were used for the collection of data. Data collected were analysed using SPSS software. Fifty respondents were selected from both the Junior/Senior staff and Sen-ior Members of the KNUST Main Library for the study. It was revealed from the study that knowledge sharing takes place a lot in the Library but this often comes as a by-product of ordi-nary conversations and discussions. Many respondents overwhelmingly stated that they share their experiences with their colleagues. More attention to be given to formal forms of knowledge sharing in the Library and the creation of culture of external knowledge sharing were some of the recommendations made to help improve on the level of knowledge sharing in the Library.